2016
DOI: 10.5603/aa.2016.0005
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous left iliac vein rupture — case report

Abstract: Spontaneous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A completely different venous pathology was described by Kalender et al [ 276 ], who reported the rupture of an iliac vein leading to a retroperitoneal haematoma. The patient presented with LBP associated with abdominal pain [ 276 ].…”
Section: Resultsmentioning
confidence: 82%
“…A completely different venous pathology was described by Kalender et al [ 276 ], who reported the rupture of an iliac vein leading to a retroperitoneal haematoma. The patient presented with LBP associated with abdominal pain [ 276 ].…”
Section: Resultsmentioning
confidence: 82%
“…After a full-text review, 82 articles were considered for inclusion. Of these, 20 articles were excluded, resulting in the inclusion of 63 case reports comprising 68 patients, including the current case, from 1961 to 2022 [ [1] , [2] , [3] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. The case reports were published in various languages, including English (n = 46), Spanish (n = 6), Japanese (n = 4), Chinese (n = 3), Portuguese (n = 1), Danish (n = 1), French (n = 1), and German (n = 1) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…After full-text screening, 76 cases were included in this systematic review presented in 64 studies from all over the world ( Table 1 ). 2 , 3 , 6 - 67 Most patients underwent open surgery, the first reported in 1961. Endovenous procedures were reported since 2004.…”
Section: Resultsmentioning
confidence: 99%